Association of GSTM1 and GSTT1 genes insertion/deletion polymorphism with colorectal cancer risk: a case-control study of Khyber Pakhtunkhwa population Pakistan - Zubair, Hina; Aurangzeb, Javeria; Zubair, Bushra; Imran, Muhammad (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate the genetic association of glutathione S transferase M1 and glutathione S transferase T1 genes insertion/deletion polymorphism with the risk of colorectal cancer. Method: This case-control study was conducted March 2018 and November 2019 at the University of Peshawar, Peshawar, Pakistan, and comprised blood samples from colorectal cancer patients and age- and gender-matched controls. Deoxyribonucleic acid was extracted from blood samples, and glutathione S transferase M1 and glutathione S transferase T1 genotyping was performed using polymerase chain reaction at the Institute of Radiation and Nuclear Medicine, Peshawar. Data regarding age, gender, location, smoking status, cancer stage and node involvement was collected on a predesigned proforma. Data was analysed using Minitab 17. Results: The frequency of glutathione S transferase M1 was was significantly associated with colorectal cancer risk (p<0.01), while glutathione S transferase T1 null genotype showed non-significant association (p<0.43). The association between the combined deletion of glutathione S transferase M1 and glutathione S transferase T1 polymorphism and the colorectal risk was significant (p=0.011). Glutathione S transferase M1 and glutathione S transferase T1 deletions had non-significant association with age, smoking status, dwelling and tumour location (p>0.05) when compared with the wild genotypes in colorectal cancer cases. Conclusion: Glutathione S transferase M1 gene deletion was found to be associated with the risk of colorectal cancer development. Key Words: Colorectal cancer, Detoxification, GSTM1, GSTT1, Polymorphism. Continuous...